Early-Middle Pleistocene deep circulation in the western subtropical Atlantic: Southern Hemisphere modulation of the North Atlantic Ocean - Ferretti, P.; Shackleton, N. J.; Rio, D.; Hall, M. A. (Geological Society, London, Special Publications, 2005)
Early-Middle Pleistocene climate and deep ocean hydrography have been reconstructed using oxygen and carbon isotope ratio measurements in planktonic and benthic foraminifera from a high-deposition-rate sedimentary succession recovered at the Bermuda Rise, in the northern Sargasso Sea (Ocean Drilling Program Leg 172, Site 1063). The site’s water depth makes it sensitive to changes in the balance between North Atlantic Deep Water (NADW) and Antarctic Bottom Water (AABW) in the deep North Atlantic, allowing the evaluation of perturbations in deep water production at different timescales. Millennial-scale fluctuations, superimposed on the longer period oscillations of orbital origin, occurred during all the observed climate states. The highest amplitude sub-Milankovitch fluctuations were mainly associated with interglacials, particularly after the intensification of the glacial regime at c. 900 ka. Using the benthic carbon isotope signal as a water mass tracer, and by comparing the δ13C record to a suite of drill sites in the North Atlantic and Pacific oceans, it has been possible to infer that the relative strength of AABW production varied through time, as did that of NADW. A scenario in which the two different source components of deep water can undergo dramatic changes in their circulation regime through time should be taken into consideration when evaluating the role of thermohaline circulation in global climate change.